The Speech Acts of Illusory Islamic Reflection in Musleem.id Instagram Account Uploads: A Pragmatic Study - Muhamad Sukhin Annur; Walaa Osama (Jurnal Sastra Indonesia, 2026)
This study examines the use of speech acts in pragmatics, with a primary focus on the illocutionary speech acts of the Musleem.id Instagram account. The purpose of this study is to identify the types of illocutionary speech acts contained in the posts of the Musleem.id Instagram account and describe its functions based on the context of the speech. This study uses two approaches, namely methodological and theoretical. The methodological approach used is descriptive qualitative. The theoretical approach uses pragmatic analysis. The data source of this study is the posts of the Musleem.id Instagram account containing illocutionary speech acts. In this study, Searle's theory is used, which divides illocutionary speech acts into five types, namely representative, directive, expressive, commissive, and declarative, with the existence of evidence from the posts. The results of the study analyzing illocutionary speech acts in Muslim uploads.id Instagram account found 21 data, consisting of 4 representative speech act data (the functions found were indicating and stating), 8 directive speech act data (the functions found were inviting and suggesting), 6 expressive speech act data (the functions found were criticizing and stating),  2 commissive speech act data (the functions found were promising and being able), and 1 declarative speech act data (the functions found were prohibiting). The benefits of this research can theoretically contribute to linguistic studies, particularly in pragmatics, especially in illocutionary acts. In practical terms, this research can help readers better understand illocutionary speech acts.